Problems with exclusive breast feeding– A study in state referral hospital at Falkawn, Mizoram, India - Dr.F.Elizabeth Lalhmangaihzuali; Dr. Zarzoliana; Dr. Zorinsangi Varte (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Exclusive breastfeeding is the best way to feed children below the age of 6 months. However, there are problems that hinder exclusive breastfeeding. The aim of this study is to identify problems hindering exclusive breastfeeding. Methods: This cross-sectional descriptive study is carried out at State Referral Hospital, Falkawn, Aizawl, Mizoram, India from 1st April to 30th June 2018, covering 200 children aged 6 months to 24 months old and their mothers on occasion of systematic visit to breastfeeding counselling centre. Results: Exclusive breastfeeding is practiced by 80% of the mothers in spite of the problems faced by mothers during lactation. Absence of lactogenesis and working condition of the mothers represent 45% of the reasons for not practicing exclusive breastfeeding. Mothers’ condition plays an important role as post partumdepression (5%) and other medical illness (7.5%) effect exclusive breastfeeding. Mothers working in public sector (62.5%) and employees (64.5%) poorly practiced exclusive breastfeeding as compared to housewives (85.3%). Single mothers (60%) breastfeed less than married mothers (81.6%). Families with one parentas financial contributor adopted exclusive breastfeeding better (89.7% versus 59.3%, p<0.05) where most of the mothers are housewives (85.3%). The proportion of exclusive breastfeeding is very high among mothers with low education level (87.5%). It was observed that exclusive breastfeeding practice increases with the increase in baby’s ranks (87.5% in fourth rank and above). Conclusion: In spite of all problems encountered, exclusive breastfeeding is practiced by 80% of the mothers, showing the effectiveness of breastfeeding counselling of mothers by breastfeeding counsellors.